Evaluation of Learning for Children with Special Needs at SDN Gunung Sekar 2 Sampang - Nailatur Rizqiyah; Masti Yanto; Umarul Faruk; Moh Elman (Indo Publishing, 2025)
This study aims to evaluate the learning process of children with special needs at SDN Gunung Sekar 2 Sampang. The evaluation was conducted to determine the extent of the effectiveness of learning strategies, availability of facilities, and the role of teachers in meeting individual student needs. The research method used was a qualitative approach with observation, interview, and documentation techniques. The subjects of the study included class teachers, students with special needs, and the principal. Initial results showed that there were quite good efforts in implementing an inclusive learning approach, although there were still limitations in terms of resources and teacher training. The findings of this study emphasize the importance of developing teacher competencies and providing adequate supporting facilities to support the learning of children with special needs. This evaluation also recommends the need for cooperation between schools, parents, and related agencies to create a friendly and adaptive learning environment. With ongoing evaluation, it is hoped that SDN Gunung Sekar 2 Sampang will be able to provide more optimal and inclusive education services for all its students